A Good Place to Live: Plants and People at the Santa Elina Rock Shelter (Central Brazil) from Late Pleistocene to the Holocene. Issue 2 (June 2020) - Scheel-Ybert, Rita; Bachelet, Caroline
Abstract : The Santa Elina rock shelter (Central Brazil) was recurrently occupied from the Late Pleistocene to the Late Holocene. We compare sets of previously published anthracological analyses with new data to reconstruct the landscape, vegetation, and climate over the several thousand years of occupation, providing information on firewood management from about 27, 000 to about 1500 cal BP. Laboratory analyses followed standard anthracological procedures. We identified 34 botanical families and 84 genera in a sample of almost 5, 000 charcoal pieces. The Leguminosae family dominates the assemblage, followed by Anacardiaceae, Bignoniaceae, Rubiaceae, Euphorbiaceae, and Sapotaceae. The area surrounding the shelter was forested throughout the studied period. The local landscape was formed, as it is today, by a mosaic of vegetation types that include forest formations and open cerrado . Some regional vegetation changes may have occurred over time. Our data corroborate the practice of opportunistic firewood gathering in all periods of site occupation, despite a possible cultural preference for some taxa. The very long occupation of Santa Elina may be due not only to its attractiveness as a rock shelter but also to the continuously forested vegetation around it. It was a good place to live.